Cyprus Hydrocarbons: Lessons from the Nigerian Experience - Kaniye S.A. Ebeku (European Scientific Journal, ESJ, 2018)
Hydrocarbons/oil is still the greatest source of energy in the world, although its importance is diminishing with the development of alternative/environment-friendly sources of energy such as wind-power and solar energy. For most oil-producing countries, hydrocarbons/oil revenue is a significant source of income. For instance, this is the case in Nigeria, whose economy depends heavily on oil revenue. Even so, natural resource wealth (hydrocarbons/oil, etc.) can also be a curse as it may cause poverty in the country, breed corruption, precipitate human rights abuses and other contradictions. This is the experience of some oil-producing countries such as Nigeria, Libya, Ecuador, and Algeria. The recent discovery of hydrocarbons in Cyprus is surely an important development for the country. However, given the negative experience of other resource-rich countries it is important to explore the possible lessons Cyprus may learn from such experience that could help her maintain a healthy economy when hydrocarbons revenue starts rolling in as projected, in 2022. This is the main objective of this paper and the Nigerian experience will be used as a case-study. Presently, the Cyprus economy without hydrocarbons revenue is strong and healthy; income is derived from diverse sources such as tourism, services and agriculture. This paper argues that Cyprus should learn from the experience of Nigeria and avoid abandoning other sources of revenue when it starts earning hydrocarbons revenue so that it would not suffer ‘Dutch disease’. Moreover, from the experience of Nigeria, Cyprus should take precautionary steps to check hydrocarbons industry related corruption, internal conflicts and other paradox which hydrocarbons could bring about. In conclusion, the paper recommends that the Cyprus economy should remain diversified in order to avoid the negative experience of Nigeria.